HNF4α inhibits the malignancy of intrahepatic cholangiocarcinoma by suppressing the Wnt signaling pathway - Bo-Nan Xu; Cheng-Hong Ding; Yi-Long Liu; Yuan-Yuan Luo; Juan Deng; Shu-Qing Liu; Meng-Chao Xiao; Nan Jiang; Xin Zhang; Wen-Ping Xu; Wei-Fen Xie (Translational Oncology)
Previous studies have demonstrated that intrahepatic cholangiocarcinoma (ICC) may derive from transdifferentiation of hepatocytes, so transforming ICC cells into hepatocytes could be a potential strategy for treating ICC. Hepatocyte nuclear factor 4α (HNF4α), a master transcription factor in the liver, has been demonstrated to induce the differentiation of hepatocellular carcinoma, while its effects on ICC remains unclear. Ivosidenib, an isocitrate dehydrogenase 1 (IDH1) inhibitor, is a novel targeted drug for ICC patients. However, drug resistance limits its clinical efficacy. In the present study, we found that the downregulation of HNF4α expression was associated with aggressive tumor behavior and poor prognosis in ICC patients. Upregulation of HNF4α inhibited proliferation, migration, invasion and colony-formation ability, increased the expression of hepatocyte functional genes in ICC cells in vitro, and suppressed the growth of subcutaneous tumors in vivo. Importantly, HNF4α adenovirus treatment significantly reduced the tumor burden of Akt/NICD-induced primary ICC in mice. Furthermore, HNF4α enhanced the sensitivity of ICC cells to ivosidenib both in vitro and in vivo. RNA sequencing revealed that HNF4α suppressed several cancer-related pathways, including Wnt signaling pathway. The agonist of Wnt signaling pathway partially blocked the inhibitory effect of HNF4α on the proliferation and resistance to ivosidenib of ICC cells. These results identify HNF4α as a tumor suppressor for ICC and a potential sensitizer to ivosidenib in ICC patients. The reintroduction of HNF4α might help achieve more effective and precise targeted therapy, benefiting the survival of patients with ICC.